2020
DOI: 10.1371/journal.pone.0238369
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and impact of body mass on performance from childhood to senior athletes in Olympic weightlifting

Abstract: Background Olympic weightlifting requires technical skills, explosive power, strength, and coordination. Weightlifters can be competitive within a range of morphological characteristics due to competition body weight classes. To date no studies have examined when sex differences arise in weightlifting and the impact of body mass on performances at different ages. Objectives To examine when sex-related differences emerge, to quantify the influence of body mass on performances at different ages, and to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…In the case of the stature, the data of the Spanish weightlifters (179.5 ± 8.33 [ 30 ] and 172.1 ± 6.3 cm [ 31 ] for men; and 166.3 ± 7.39 cm for women) are similar to those of our sample (176.18 ± 6.85 cm for men; and 166.94 ± 4.11 cm for women). Other studies also show similar weights and statures for men and women weightlifters [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…In the case of the stature, the data of the Spanish weightlifters (179.5 ± 8.33 [ 30 ] and 172.1 ± 6.3 cm [ 31 ] for men; and 166.3 ± 7.39 cm for women) are similar to those of our sample (176.18 ± 6.85 cm for men; and 166.94 ± 4.11 cm for women). Other studies also show similar weights and statures for men and women weightlifters [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 55%
“…It has been previously reported that a short stature implies an advantage in this sport discipline [ 30 ] but, in general terms, the taller weightlifters are also the ones whose body mass is higher [ 12 , 32 ]. Because in weightlifting body mass determines the weight class the athletes compete in, body composition and segments’ length become extremely relevant for successful performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations